How Does Industry Affect Firm Financial Structure? - MacKay, Peter; Phillips, Gordon M. (Review of Financial Studies, 2005)
We examine the importance of industry to firm-level financial and real decisions. We find that in addition to standard industry fixed effects, financial structure also depends on a firm's position within its industry. In competitive industries, a firm's financial leverage depends on its natural hedge (its proximity to the median industry capital–labor ratio), the actions of other firms in the industry, and its status as entrant, incumbent, or exiting firm. Financial leverage is higher and less dispersed in concentrated industries, where strategic debt interactions are also stronger, but a firm's natural hedge is not significant. Our results show that financial structure, technology, and risk are jointly determined within industries. These findings are consistent with recent industry equilibrium models of financial structure. Copyright 2005, Oxford University Press.